The Role of the Principal in Improving Teacher Motivation at State Junior High School 19, Banda Aceh - Badruzzaman, Badruzzaman; Emsa, Tasmiati; Nuryadin, Wiwoho (Dinasti Publisher, 2023)
This study aims to determine the work motivation of educators, the role of the Principal in improving the work motivation of educators and the obstacles faced in improving the work motivation of educators. In this study, the researcher used a descriptive Qualitative research type. This research was conducted at SMP Negeri 19 Percontohan Banda Aceh. The subjects in this study were the Principal, Deputy Head of Student Affairs, Deputy Head of Curriculum, Head of Teaching and Educators. Based on the results and discussion of the study, it can be concluded that: 1. The role of the Principal in improving the motivation of educators at SMP Negeri 19 Percontohan Banda Aceh is the role as an Educator, Manager, Administrator, Supervisor, Leader, Innovator and Motivator. In dividing and determining the tasks needed, it has been carried out by the Principal to improve Teacher competence. In determining the division and determining tasks, the Principal holds a Work Meeting before entering the new School Year involving the entire school community. That learning devices are very much needed, this is a reference for teachers in more focused PBM activities and ensuring the quality of education. Recruiting teachers is the role of the Principal. Recruiting teachers is a process of finding and finding the right people in the school environment. Thus, recruiting teachers is a very important thing to do based on the needs and requirements determined by the school. Educator motivation in motivating learning requires more complete facilities and infrastructure and in developing students, a learning model needs to be carried out which can be said to be a meaningful learning approach for students. In managing the learning that will be planned, it is necessary to support four variables that are managed optimally, namely student management, management of teaching staff, learning procedures and management of the classroom environment. Awards are very important to stimulate teachers to teach more actively and enthusiastically. The principal gives awards to highly motivated and high-achieving teaching staff. 2. The principal's obstacles in increasing the motivation of educators at SMP Negeri 19 Percontohan Banda Aceh are the existence of educators who do not recognize their low quality, especially in mastering the class and facilities and infrastructure that are still incomplete.